Influence of anatomy and basic density on specific cutting force for wood from Corymbia citriodora Hill & Johnson - de L. Melo, Luiz-E.; M. da Silva, José-R.; Napoli, Alfredo; Lima, José-T.; R. Nascimento, Débora-F. (Forest Systems, 2015)
Aim of the study: The aim of this study was to evaluate the influence of xylem tissue cell structure, determined through biometry and basic density of the wood from Corymbia citriodora Hill & Johnson on consumption of specific 90º-0º longitudinal cutting force. Area of study: The study area was in the region of the Vale do Rio Doce - Minas Gerais, Brazil. Material and methods: A diametrical board with dimensions of 60 x 18 x 5 cm (length x width x thickness, respectively), with more than 1.3 m from the ground, was removed. In machining trials, a 400 mm diameter circular saw was used, with 24 “WZ” teeth, feed rate of 10 m.min-1, cutting speed of 61 m.s-1, and maximum instantaneous torque of 92.5 N.m. During cutting, test specimens were removed with alternated and parallel 1.5 cm edges in 6 radial positions, which were used for biometric determination of cell structure and basic density. Main results: It was observed that wood basic density, vessel diameter, fiber wall thickness, fiber wall fraction and fiber wall portion were directly proportional to the specific cutting force. In contrast, vessel frequency and fiber lumen diameter proved to be inversely proportional to cutting force. Research highlights: This work provides important values of quantification of influence of xylem tissue cell structure, determined through biometry and physical properties of the wood that may be used to prediction of consumption of specific cutting force. Keywords: wood machining; wood properties; optimization of the process.